2019
DOI: 10.20396/bjos.v18i0.8657264
|View full text |Cite
|
Sign up to set email alerts
|

Impact of oral medicine training on oral cancer-related knowledge among undergraduate dental students

Abstract: Aim: The aim of this study was to evaluate knowledge and attitudes regarding potentially malignant oral lesions and oral cancer among undergraduate dental students with or without training in the oral medicine. Methods: A cross-sectional study was undertaken to assess all undergraduate dental student (1st to 5th year) in two private universities in the state of Paraná, Brazil. A structured questionnaire about knowledge regarding potentially malignant oral lesions, continuing education, and different approaches… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 22 publications
1
2
0
1
Order By: Relevance
“…Similar results were obtained by Galina et al [21] in Brasil, where dental students identified actinic cheilitis in a percentage of 2%, while erythroplasia was identified by 32% of students.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Similar results were obtained by Galina et al [21] in Brasil, where dental students identified actinic cheilitis in a percentage of 2%, while erythroplasia was identified by 32% of students.…”
Section: Discussionsupporting
confidence: 89%
“…The questionnaire used in this study was designed after an extended review of the literature [16,21,24,[27][28][29], and it was adequate for the study's purpose, namely the assessment of knowledge and attitude towards the practice and primary prevention of oral cancer, in general, and the HPV infection, in particular.…”
Section: The Study Instrumentmentioning
confidence: 99%
See 1 more Smart Citation
“…Nos estudos realizados nos continentes europeu e americano o tabagismo foi declarado corretamente como fator etiológico mais importante para o surgimento do câncer bucal, mesmo sem estar associado aos demais fatores de risco (Domitrescu, et al, 2014;Frola & Barrios, 2017;Galina, et al, 2019;Kumar, et al, 2016;Soares, et al, 2014). Entretanto, isso não foi verificado em países da Ásia (Bhagavathula et al, 2015;Fotedar, et al, 2015).…”
Section: Pokhrel E Khadka 2020 Nepalunclassified